Inflation uncertainty, disagreement and monetary policy: Evidence from the ECB Survey of Professional Forecasters - Alexander Glas; Matthias Hartmann (University of Heidelberg, Department of Economics, 2016)
We analyze the determinants of average individual inflation uncertainty and disagreement based on data from the European Central Bank's Survey of Professional Forecasters. We empirically confirm the implication from a theoretical decomposition of inflation uncertainty that disagreement is an incomplete approximation to overall uncertainty. Both measures are associated with macroeconomic conditions and indicators of monetary policy, but the relations differ qualitatively. In particular, average individual inflation uncertainty is higher during periods of expansionary monetary policy, whereas disagreement rises during contractionary periods.
urn:nbn:de:bsz:16-heidok-204344
Keywords: 330; Inflation uncertainty; Disagreement; Density forecast; Central banking; Survey of Professional Forecasters; Inflation; Inflationserwartung; Geldpolitik; Wirtschaftsprognose; EU-Staaten